Virginia Woolf and Post-Impressionism: French Art, English Theory and Feminist Practice - Jane Goldman (Miscelánea: A Journal of English and American Studies)
Roger Fry's historic exhibition of 1910, "Manet and the Post-Impressionists", was a defining moment in avant-garde aesthetics, marking European modernism's revolutionary impact on the practices of British artists. But it also marked the start of British formalist theorists' influence on the critical apparatus for modernism. It is often cited to explain Virginia Woolf's enigmatic statement, in "Mr. Bennett and Mrs. Brown" (1924): "on or about December 1910 human character changed". The formalist aesthetics of Roger Fry and Clive Bell with which this date has become linked are also invoked in readings of To the Lighthouse (1927) to explain the painting practice of Lily Briscoe and the modernist aesthetics of Woolf herself. But 1910 saw other events surrounding the exhibition that we might acknowledge as relevant: in particular, the suffragette activism occurring at the time of the exhibition, culminating in the notorious demonstration on "Black Friday". Woolf's manifesto on 1910 seems to resonate both with the formulations by Fry and Bell on European art and with the formulations and practices of British suffragist artists. The stained-glass artist and organiser of suffragist colours, Mary Lowndes, published a number of essays in 1910 and 1911 which are of particular interest. The combined influences of French art, English formalist theory, and suffragist aesthetics may be at work in Woolf's Künstlerroman of 1927.